Overview of legal and administrative approaches to manage human-wildlife conflicts in Malaysia - Mustafa, Maizatun; Ariffin, Mariani; Sabran, Siti Fatimah; Tan, Sarah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Human-wildlife conflicts result when the actions of humans or wildlife have an adverse impact upon the other. This paper presents an overview of Malaysia’s legal and administrative approaches to manage human-wildlife conflicts (HWC). Firstly, the paper reviews the status of wildlife in Malaysia and the current conflicts involving man and wild animals that happen both in urban and rural areas. Then it identifies government’s policy relating to land-use planning as well as wildlife conservation, and examines how such policies have shaped HWC. While urbanization and agricultural expansion are considered main factors that contribute towards such conflict, environmental law and relevant administrative instrument on the other hand can play vital roles to support the management and mitigation of HWC. For this purpose, the article examines existing legal provisions and administrative strategy applicable in Malaysia to manage and mitigate conflicting interests of human and wildlife. The examination concludes that law and institutions have important roles to play in managing and mitigating HWC. Mitigation measures through the provisions of law and institutional strategy that take into consideration biological, economic and social factors can effectively narrow down the conflicts. At the same time such measures also help towards environmental conservation, and enhancement of human welfare, health and safety